Bringing technology into the boardroom/ edited by the European Institute for Technology Management. (Palgrave Macmillan, 2003)
Europe is waking up to the challenge of technology and innovation. This text brings together practice, research findings and thinking in a way that addresses top management requirements. The goal is to secure the economic future of the firm, in the context of a sustainable industry and society.